Timi Flow Between Streptokinase and Alteplase in Successful Fibrinolytic - Ashrinda, Dika; Hasan, Refli; Andra, Cut Aryfa; Muhtar, Zulfikri; Hasan, Harris (Sumatera Medical Journal, 2019)
STEMI with onset≤12 hours, necessary to take Primary Percutaneous Coronary Intervention (pPCI), but if there is no facility, another therapy is fibrinolytic, to improve blood flow in the coronary artery and myocardial function, thus reducing infarction expansion. This is a retrospective study in STEMI patients onset≤12 hours, had performed successful fibrinolytic with Streptokinase (SK) and Alteplase (tPA) from January 2015 to August 2017. TIMI flow was assessed by coronary angiography. There were 54 patients who had performed successful fibrinolytic therapy with SK and tPA; each group had 27 patients. In the SK group, there were nine patients (33.3%) with TIMI flow 2 and 18 patients (66.7%) with TIMI flow 3. While in the tPA group there were 11 patients (40.7%) with TIMI flow 2, 16 patients (59.3%) with TIMI flow 3, (p=0.573). There is no difference in TIMI flow between SK and tPA on STEMI patients after success fibrinolytic therapy.